Technology Acceptance Model Android Puzzle Games Based on Banten Local Culture for Early Childhood Education - Asmawati, Luluk (Universitas Pendidikan Ganesha, 2024)
The background to the development of an android-based multimedia model for early childhood cognitive learning requires an analysis of acceptance of puzzle games in early childhood. The aim of the research was to analyze the results of the Banten ancient mosque android puzzle game on the cognitive development of early childhood. The research methodology used a survey of 30 young children. Data collection used observation and interviews. Data analysis was carried out descriptive qualitative. The findings from the research were perceived usefulness 68%, perceived ease of use of Android puzzle games 67%, and user acceptance 88%; The results of the t test obtained a sig value of 0.472 more than 0.05 (0.472 > 0.05), so that the decision to accept Ho could be obtained. This means that there were no differences in student learning outcomes in terms of gender; The results of the t test obtained a sig value of 0.507, more than 0.05 (0.472 > 0.05), so that the decision to accept Ho could be obtained. This means that there was no difference in student learning outcomes in terms of the age range of 5 years and 6 years. The conclusion is that the acceptance of Android puzzle games is very good and can improve the cognitive learning of early childhood children aged 5-6 years. The implication of the results of this study was that the android puzzle game can be used as a cognitive learning medium for children aged 5-6 years. Android puzzle game had an impact on children's learning motivation.